The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1123/japa.2012-0018
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Long-Term Physical Activity Intervention on Serum Uric Acid in Older Adults at Risk for Physical Disability

Abstract: Observational studies show a relationship between elevated serum uric acid (UA) and better physical performance and muscle function. The purpose of this paper was to determine whether regular participation in an exercise intervention, known to improve physical functioning, would result in increased serum UA. For this study, 424 older adults at risk for physical disability were randomized to participate in either a 12-mo moderate-intensity physical activity (PA) or a successful aging (SA) health education inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…However, smoking could also reduce endogenous production of UA (an antioxidant) via inducing oxidative stress. Similarly, the relationship between physical activity and UA status is complicated; moderate–vigorous physical activity results in a modest increase in systemic concentration of UA and light‐intensity physical activity may be associated with the lower UA concentrations in obese individuals . We did not observe a significant relationship between diet and future risk of hyperuricemia.…”
Section: Discussionmentioning
confidence: 53%
“…However, smoking could also reduce endogenous production of UA (an antioxidant) via inducing oxidative stress. Similarly, the relationship between physical activity and UA status is complicated; moderate–vigorous physical activity results in a modest increase in systemic concentration of UA and light‐intensity physical activity may be associated with the lower UA concentrations in obese individuals . We did not observe a significant relationship between diet and future risk of hyperuricemia.…”
Section: Discussionmentioning
confidence: 53%
“…Antioxidant properties of uric acid have been attributed to the capacity of reacting with biological oxidants [40]. Thus, the increases observed in this parameter after the padel matches could be a mechanism to face the greater production of reactive oxygen species (ROS) cause by the physical exercise [44]. On the other hand, the increases observed in urea after the SC could be associated with an enhanced protein catabolism due to the game intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to our results, in the study of Nishida et al [ 51 ], moderate intensity PA was inversely correlated with UA level in obese individuals. On the other hand, Beavers et al [ 52 ] identified about 5% higher values of UA in older adults after 12-month moderate intensity PA intervention as compared with subjects who participated only in a successful aging health education intervention. Ideally, exercise training should be able to reduce proinflammatory levels of UA to antioxidant and protective levels.…”
Section: Discussionmentioning
confidence: 99%